The effect of power alternation frequency during cycling on metabolic load and subsequent running performance - Fraser Hill, C.; St Clair Gibson, A. (Journal of Science and Cycling, 2012)
The purpose of this study was to determine whether the frequency of power output alternation during cycling affects subsequent running performance. Eleven male triathletes completed a graded cycle test to determine peak oxygen uptake and the corresponding power at 35% delta. Two performance tests were then conducted, each comprising of a thirty minute cycling protocol followed by a 5 km free pace run. Mean cycling power was equal for both trials (35% delta), however the frequency of power alternations differed. In one trial cycling power output alternated every five minutes, whereas in the other trial cycling power output alternated every one minute. Power was set to alternate 15% above and below the 35% delta value. No significant difference was found between trials for the subsequent 5 km running performance time (P = .63). A significant difference was observed for overall mean heart rate between cycle trials (P = .045), however no significant difference was observed for overall mean oxygen uptake, minute ventilation, respiratory exchange ratio, blood lactate, rating of perceived exertion or pedal cadence (P > 0.05). When data was divided into 5 minute epoch stages rating of perceived exertion was significantly different between cycle trials at epochs three (minutes 10-15; P = .046) and five (minutes 20-25; P < 0.001). We conclude that when power is alternated equally during cycling, the frequency of power change (maximum of five minutes, minimum of one minute) does not affect subsequent running performance.